Impact of Climate Change on Vector Borne Diseases and Public Health: A Review - Kumar , D. Veera Nagendra; Krishnaiah, C. Venkata; Seethamma, G.; Rajasekar, G.; Reddy , C. Nageswara; Srineetha , U. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Vector-borne diseases endure to contribute knowingly to the global problem of disease, and cause epidemics that disturb health security and cause wider socioeconomic effects around the world. Climate affects by pathogens it causes diseases that spend part of pathogens lifecycle host outside, visible to the environment. The main significant routes of spread of climate sensitive diseases are by arthropod (insect and tick) vectors, in food and water. Climate change has the possible to impact the earth's biological systems, The impacts of climate change on health are wide-ranging and diverse. They encompass the rise in fatalities and illnesses caused by more frequent and intense extreme weather events like heatwaves, storms, and floods. Climate change also disrupts food systems, leading to an increase in diseases transmitted through food, water, and vectors. Due to climate change emerging nations with partial resources are expected to face a host of health effects, including vector-borne and water-borne diseases such as cholera, malaria and dengue. Climate change can impact the transmission dynamics, geographical expansion, and recurrence of vector-borne diseases through various channels. These include its direct influence on the pathogens, vectors, non-human hosts, and humans involved. Furthermore, climate change has the potential to modify entire ecosystem habitats, including urban environments, thereby influencing the proliferation or decline of vectors and non-human hosts. This article analyses common and prevalent infectious diseases in India, their links to climate change.